2002
DOI: 10.1073/pnas.102165099
|View full text |Cite
|
Sign up to set email alerts
|

Segregation distortion induced by wild-type RanGAP in Drosophila

Abstract: Segregation Distorter (SD) is a meiotic drive system in Drosophila that causes preferential transmission of the SD chromosome from SD͞SD ؉ males owing to the induced dysfunction of SD ؉ spermatids. The key distorter locus, Sd, is a dominant neomorphic allele encoding a truncated, but enzymatically active, RanGAP (RanGTPase-activating protein) whose nuclear mislocalization underlies distortion by disrupting the Ran signaling pathway. Here, we show that even wild-type RanGAP can cause segregation distortion when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 24 publications
3
61
0
Order By: Relevance
“…Indeed, as far as we are aware, the only other driver for which we have sufficient genetic resolution, the autosomal Segregation distorter of D. melanogaster, also displays a duplication. In that case, it has been demonstrated that gene dosage alone, either of the key distorter locus or of a modifier locus, can confer drive (Kusano et al 2002).…”
Section: à4mentioning
confidence: 99%
“…Indeed, as far as we are aware, the only other driver for which we have sufficient genetic resolution, the autosomal Segregation distorter of D. melanogaster, also displays a duplication. In that case, it has been demonstrated that gene dosage alone, either of the key distorter locus or of a modifier locus, can confer drive (Kusano et al 2002).…”
Section: à4mentioning
confidence: 99%
“…While wild-type RanGAP localizes to the cytoplasm, SdRanGAP is retained in the nucleus due to its truncated NES, potentially altering the GTP gradient required for Ranmediated nuclear transport (Gorlich and Mattaj 1996;Gorlich and Kutay 1999b;Merrill et al 1999;Kalab et al 2002). In the proper genetic background, nuclear localization of even wildtype RanGAP is sufficient to cause distortion, suggesting that nuclear enzymatic activity of RanGAP causes abnormal nuclear retention of Ran cargo and sperm dysfunction in SD (Kusano et al 2001(Kusano et al , 2002.The relative strength of Segregation Distorter chromosomes is dependent upon several modifiers distributed along the second chromosome ( Figure 1A). The best studied of these, Enhancer of SD [E(SD)], is located in the h35 heterochromatic region of chromosome 2L (Ganetzky 1977;Brittnacher and Ganetzky 1984).…”
mentioning
confidence: 99%
“…17,18 In Sd mutants RanGAP is enzymatically active and present inside of the nucleus, and it is this mis-localization that causes the observed segregation distortion. 18,19 The Rsp locus "responds" to the presence of the SD chromosome. Rsp exists in several different allelic forms, usually described as: Rsp i , which is insensitive to the action of Sd; Rsp s , which is sensitive to Sd; and Rsp ss , which is "supersensitive" to the action of Sd.…”
Section: Introductionmentioning
confidence: 99%